(untitled) (Revista Venezolana de Salud Pública, 2021)
To determine the risk factors for parasitosis in children under 5 years of age in a Human Settlement - Peru, 2020. An analytical, observational, prospective study was carried out; with a cross-sectional, relational design with a quantitative approach in 90 children and mothers applying a questionnaire of risk factors and to determine parasitosis. It was carried out through the analysis of small stool samples. Likewise, for the data analysis the descriptive statistics of the SPSS version 25 program was used and for the inferential analysis the bivariate analysis of the chi-square test was used with a significance of p <0.05. Results: 70.0% of children presented parasitosis. The group most affected 46.7% were children from 5 to 6 years old; in terms of sex, 53.3% of the male sex. The most prevalent type of parasite in 31.0% was Escherichia Coli cyst. The housing factors that were related to parasitosis were the dirt floor, 71.1%; not having drinking water 59.0%. The risk factors for parasitosis were; sociodemographic factor overcrowding 65.7%; Family monthly income <500 73.1%. Regarding environmental factors and behavior, the raising of animals within the home was 63.5%. And in the factor of eating habits, the consumption of non-boiled water was 35.7%. it is concluded that there are risk factors for parasitosis in children under 5 years of age.